ANALISIS KESULITAN MAHASISWA PENJASKESREK SEMESTER AKHIR DALAM PROSES PENYUSUNAN TUGAS AKHIR DI UNIVERSITAS SERAMBI MEKKAH TAHUN 2024 - junaidi, Junaidi; Fajri, Mahlil; Sofya, Bungsu Amelia; Nuhari, Insan (Jurnal Sosial Humaniora Sigli, 2024)
This study aims to determine the difficulties of final semester Penjaskesrek study program students in compiling their final thesis assignments at the Fkip, Department of Penjaskesrek. This study uses a qualitative design. The subjects of the study were final semester Penjaskesrek study program students who were working on their final thesis assignments. The object of this study was to analyze the difficulties of final semester Penjaskesrek study program students in compiling their final thesis assignments. The data collection technique used was interviews. The research instrument used was interview guidelines. The data analysis technique used the Miles and Huberman model. The data analysis process includes data reduction, data presentation, and drawing conclusions from the research results. The results of the study showed that Penjaskesrek students experienced difficulties in compiling their theses. The difficulties experienced include: (1) Lack of student understanding of research methodology so that students have difficulty in completing their final assignments; (2) The latest semester final assignment guidelines have not been socialized by students, resulting in students receiving less information about the semester final assignment guidelines so that many students still use the previous year's guidelines; and (3) Students' interest in looking for references for final semester assignment guidelines is still lacking, the impact of which is that students are less enthusiastic about looking for the latest guidelines. Keywords: Difficulty, compilation, assignments, students, physical education